A novel Wiskott–Aldrich syndrome protein mutation in an infant with thrombotic thrombocytopenic purpura. (7th January 2013) - Kawasaki, Yukako; Toyoda, Hidemi; Otsuki, Shoichiro; Iwasa, Tadashi; Iwamoto, Shotaro; Azuma, Eiichi; Itoh‐Habe, Naomi; Wada, Hideo; Fujimura, Yoshihiro; Morio, Tomohiro; Imai, Kohsuke; Mitsuiki, Noriko; et al.
Abstract Thrombotic thrombocytopenic purpura (TTP) has not yet been reported to be associated with mutations in the Wiskott–Aldrich syndrome (WAS) gene. WAS is an X‐linked recessive disorder characterized by thrombocytopenia, small platelet size, eczema, recurrent infections, and increased risk of autoimmune disorders and malignancies. A broad spectrum of mutations in the WAS protein (WASP) gene have been identified as causing the disease. In this study, we report on a 2‐month‐old Japanese boy who presented with cytomegalovirus (CMV) infection and TTP. The activity of von Willebrand factor cleaving metalloproteinase, ADAMTS13 was low and the antibody against ADAMTS13 was positive (3.6 Bethesda U/mL). Although TTP was improved by plasma exchange and steroid pulse therapy, thrombocytopenia persisted and regular transfusions of irradiated platelets were needed. Tiny platelets were found on a peripheral blood smear. CMV genome was positive in peripheral blood by polymerase chain reaction and the CMV viremia continued to persist despite intravenous gancyclovir therapy. Through direct sequencing of genomic DNA of the WASP gene in the patient, we identified a novel mutation of WASP gene: the seventh nucleotide in exon 11 (G) had been deleted (1345delG). This mutation causes a frameshift and a stop codon at amino acid 470. Western blotting demonstrated a truncated WAS protein. To our knowledge, this is the first report describing TTP in WAS patients with novel mutation in the WASP gene.